Climate and land use change impacts on Mediterranean high-mountain vegetation in the Apennines since the 1950s. (2nd January 2018) - Frate, Ludovico; Carranza, Maria L.; Evangelista, Alberto; Stinca, Adriano; Schaminée, Joop H. J.; Stanisci, Angela
Abstract : Background : High-mountain ecosystems are centres of plant diversity that are particularly sensitive to land-use and climate change. Aims : We investigated the ecological trends associated with land use and climate change since the 1950s in different vegetation types in high-mountain habitats in the central Apennines. Methods : We analysed temporal changes in: Pinus mugo scrub, calcareous subalpine grasslands and alpine scree vegetation, comparing historical and recent vegetation records from vegetation plots from two periods (1955–1980 and 1990–2014) for their ecological indicator values (Landolt temperature and nutrient indicators) and structural traits (growth forms) over time using generalised linear models (GLMs). Results : We observed significant temporal differences in the ecology and structure of the analysed habitats. In the Pinus mugo scrub we detected a reduction of subalpine and herbaceous species and in calcareous alpine screes we observed an increment of the lower montane, montane and subalpine species and of dwarf shrubs. Conversely, subalpine grasslands were stable over time. Conclusions : Ecological changes that have occurred in the Central Apennines, following changes in type and intensity of land use and recent warming are consistent with those observed in other European mountains, for which climate and land-use changes are claimed as the main driving forces.